Enhancing Intrusion Detection System Performance Using a Hybrid of Harris Hawks and Whale Optimization Algorithms - Abualhaj, Mosleh M.; Al-Khatib, Sumaya N.; Al Zyoud, Mahran; Qaddara, Iyas; Anbar, Mohammed (Engineering, technology & applied science research, 2025)
Intrusion Detection and Prevention Systems (IDPSs) play a crucial role in safeguarding online connections against unauthorized access and malicious activities. To enable efficient and effective detection and mitigation, IDPSs must continuously improve their performance due to the constantly developing nature of cyber threats. However, an IDPS is more difficult to use and less reliable when it deals with huge amounts of data. This study aimed to improve the performance of IDPSs by employing optimization algorithms to reduce the data size. Particularly, the Harris Hawks Optimization (HHO) and Whale Optimization Algorithm (WOA) were combined for feature selection. The experimental results showed that the performance of the proposed IDPS was greatly improved by combining the HHO and WOA algorithms. Combining a Random Forest classifier with the suggested HHO/WOA feature selection method achieved very high results in accuracy (99.17%), recall (98.76%), precision (98.76%), and F1-score (98.43%).